Monazite Behaviour and Time-scale of Metamorphic Processes along a Low-pressure/High-temperature Field Gradient (Ryoke Belt, SW Japan). (11th June 2018) - Skrzypek, E; Kato, T; Kawakami, T; Sakata, S; Hattori, K; Hirata, T; Ikeda, T
Abstract: Low-pressure/high-temperature metamorphic rocks exposed in the western part of the Ryoke belt (Iwakuni–Yanai area, SW Japan) include a section with increasing temperature conditions from ∼425 to 880°C. We use this setting to explore the evolution of monazite grain size, texture and composition, and variations in the whole-rock composition of 11 metapelite, metapsammite or metachert samples collected along the metamorphic field gradient. Monazite grain size increases with rising metamorphic grade, regardless of the whole-rock composition. From low- to high-grade conditions we infer: (1) the initial nucleation of monazite aggregates after allanite (∼425°C); (2) monazite coarsening and coalescence driven by incipient monazite recycling; that is, dissolution of small grains to grow larger ones by Ostwald ripening (500–600°C); (3) a first major recycling stage enhanced by fluid liberation owing to muscovite breakdown (600–630°C); (4) a second recycling stage assisted by an increase in the proportion of anatectic melt owing to biotite breakdown (> 850°C). A succession of four compositional domains is recognized in monazite. We emphasize the usefulness of comparing their Ce/ThMnz, Ce/YMnz and Th/UMnz molar ratios with those derived from whole-rock analyses to constrain the origin of each domain. Domain I, with variable ratios, reflects the progressive transfer of Th ± U from allanite to monazite at low-grade conditions. Domain II, with Ce/ThMnz matching the whole-rock values, indicates growth under rock(decimetre)-scale equilibrium conditions. Domains II and III, with Th/UMnz and Ce/YMnz departing from the whole-rock values, record the competition with zircon (for U) and garnet (for Y) during growth at peak P – T conditions. Domain IV points to Y supply by garnet resorption during retrograde chloritization (< 550°C). In the highest-grade sample, zircon grains included in garnet or cordierite show metamorphic rims with sillimanite and Si-rich inclusions. These rims formed at suprasolidus conditions (650–880°C) and yield 206 Pb/ 238 U ages of 103–97 Ma (± 5 Ma), which bracket the timing of high-temperature metamorphism. Monazite dating by electron microprobe and laser ablation inductively coupled plasma mass spectrometry reveals two age groups. For domains I–III, some relatively old 206 Pb/ 238 U ages (99–95 ± 3–5 Ma) represent minimum estimates for the timing of prograde to peak metamorphism, whereas the similar oldest 206 Pb/ 238 U age for domain IV (93 ± 7 Ma) points to rapid cooling after the temperature peak. A more dominant population of younger Th–U–Pb and 206 Pb/ 238 U dates is ascribed to age resetting by heterogeneous annealing of the monazite crystal lattice. The youngest concordant 206 Pb/ 238 U age of 86 ± 4 Ma is correlated with the end of intermediate-temperature conditions (< 200–300°C) below which monazite, in metamorphic rocks as well as in the surrounding granitoids, eventually behaved as a closed isotopic system. This contribution is dedicated to the memory of Professor Kazuhiro Suzuki, for his contribution to geochronology and Japanese geology.